Performance expectancy as a determinant of use of open access resources by lecturers in university of Ibadan, Nigeria (2017)
The research work examined the open access resources as a major source of information resources available to lecturers. Open access provides information resources to lecturers at no cost. Notable among the open access resources are Institutional Repository, Open access databases, open access journals, Author’s personal archives and open text books. Objective of this study was to examine performance expectancy, as a factor affecting the use of open access resources by lecturers in University of Ibadan. The design adopted for the study was the descriptive research and population comprised lecturers from University of Ibadan. Random sampling was used to select 174 as sample size. Questionnaire for Lecturers was used as the research instrument. The analysis was done using descriptive statistics such as frequencies and percentages, while inferential statistics such as the Pearson product moment correlation and regression analysis was used to test hypothesis at 0.05 level of significance. Majority of the lecturers (77.1%) used open access resources to publish articles in the open access medium and also refer their students for assignment completion. Open access resources were useful to most of the lecturers (76.3%): of relative advantage and very relevant to the academic activities. However, the study also revealed that Performance expectancy is a strong determinant of use of open access resources as result showed there was a significant positive correlation between performance expectancy and use of open access resources by lecturers (r= .867**; n = 152; p <0.05) by lecturers. In conclusion, performance expectancy is a strong determinant of use of open access resources by lecturers.